Answer:
x = 2
Explanation:
What is needed to solve this equation is a common denominator. With a common denominator, you can get rid of subtracted fractions.
First, factor the denominator on the left side of the equation:
![(3)/((x + 3)(x - 2)) = (2)/(x+3) - (1)/(x-2)](https://img.qammunity.org/2023/formulas/mathematics/college/ojp0dhebsct124733ty0wce2mv510vyj6a.png)
Then, create a common denominator on the right:
![(3)/((x + 3)(x - 2)) = (2)/(x+3)((x-2)/(x-2)) - (1)/(x-2)((x+3)/(x+3))](https://img.qammunity.org/2023/formulas/mathematics/college/9j9k9b4g0a20cdtvjyp0zj7xxa509cieuc.png)
![(3)/((x + 3)(x - 2)) = (2(x - 2) - 1(x + 3))/((x+3)(x-2))](https://img.qammunity.org/2023/formulas/mathematics/college/8p5vsmmgr6zj2xkg1mo9dyqzazl719pr0n.png)
Put everything on one side:
![0 = (2(x - 2) - 1(x + 3))/((x+3)(x-2)) - (3)/((x + 3)(x - 2))](https://img.qammunity.org/2023/formulas/mathematics/college/f7qowwxxumr91htv1unh2vfsmavg7iz88y.png)
![0 = (2(x - 2) - 1(x + 3) - 3)/((x+3)(x-2))](https://img.qammunity.org/2023/formulas/mathematics/college/gbl0ofvnzfxdzq4myxqzi431f5f5xc9fy7.png)
![0 = (2x - 4 - x - 3 - 3)/((x+3)(x-2))](https://img.qammunity.org/2023/formulas/mathematics/college/jgd38nwh0a8zuayl8kxwzm5ppvg7zdvq6m.png)
![0 = (x - 10)/((x+3)(x-2))](https://img.qammunity.org/2023/formulas/mathematics/college/sy5pnux8zjt4rnb9auiff35vq1n2ed991t.png)
set each term equal to zero:
x - 10 = 0
x = 10
x + 3 = 0
x = -3
x - 2 = 0
x = 2 is the answer, since it is the only answer which is listed in the multiple choice question.